TO THE QUESTION OF DIFFERENTIATION BETWEEN "THEFT" AND "ROBBERY" IN THE CRIMINAL LAW OF SPAIN - N. Yu. Volosova; O. V. Zhurkina (Вестник Кемеровского государственного университета, 2014)
Crimes against property remain the most widespread among committed crimes. The paper considers the features of legislative regulation of criminal responsibility for theft and robbery in Spain, as well as the problem of differentiating between the two crimes in the Criminal Code of Spain and a number of foreign countries. Studying the norms of criminal law of foreign countries allows considering problems of qualification of this category of crimes from various points of view.